2017
DOI: 10.1021/acs.analchem.7b00113
|View full text |Cite
|
Sign up to set email alerts
|

Complete Characterization of Cardiac Myosin Heavy Chain (223 kDa) Enabled by Size-Exclusion Chromatography and Middle-Down Mass Spectrometry

Abstract: Myosin heavy chain (MHC), the major component of myosin motor molecule, plays an essential role in force production during muscle contraction. However, a comprehensive analysis of MHC proteoforms arising from sequence variations and post-translational modifications (PTMs) remains challenging due to the difficulties in purifying MHC (~223 kDa) and achieving complete sequence coverage. Herein, we have established a strategy to effectively purify and comprehensively characterize MHC from heart tissue by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 70 publications
(209 reference statements)
1
26
0
Order By: Relevance
“…27 Compared with the bottom-up approach, middle-down MS reduces the chance of proteoform information loss by analyzing larger polypeptides (> 3 kDa) that may contain multiple PTMs and unique isoform sequences. [28][29][30] Moreover, as the typical bond cleavage of mAbs in a middle-down experiment is 50%~70%, this middle-down approach improves the bond cleavage coverage in protein characterization that is limited in top-down MS. 25,26,31 Although a variety of MS approaches have been established for the characterization of therapeutic mAbs, 32 most of them focused on the high-abundance N-linked glycoforms. 33,34 High mass accuracy from isotopically resolved high-resolution MS data could be used to increase the confidence level of protein identification with detection of PTMs and variations in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…27 Compared with the bottom-up approach, middle-down MS reduces the chance of proteoform information loss by analyzing larger polypeptides (> 3 kDa) that may contain multiple PTMs and unique isoform sequences. [28][29][30] Moreover, as the typical bond cleavage of mAbs in a middle-down experiment is 50%~70%, this middle-down approach improves the bond cleavage coverage in protein characterization that is limited in top-down MS. 25,26,31 Although a variety of MS approaches have been established for the characterization of therapeutic mAbs, 32 most of them focused on the high-abundance N-linked glycoforms. 33,34 High mass accuracy from isotopically resolved high-resolution MS data could be used to increase the confidence level of protein identification with detection of PTMs and variations in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…64,67,68,77,79,85,91,139 Additionally, a few MD studies have been carried out using the hybrid LTQ-FT-ICR-MS also. 75,84,185,186…”
Section: Mass Analyzersmentioning
confidence: 99%
“…186 Other soware, such as Pro-sightPC and MASH-Suite, which were primarily developed for analysis of TD proteomic data, have also been applied well for the purpose of analyzing MD proteomic data. 66,67,70,88,89,99,172,185 Algorithms to process the raw data of MDP for the purpose of deconvolution are, Xtract, THRASH 249 and MS-Deconv. 75,91,257 Among these, Xtract and THRASH algorithms have been used mostly to analyze FT-MS data of longer proteolytic peptides.…”
Section: Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…In a study by Kawai et al examining PTMs on MYH6, the predominant murine myosin isoform, 31 phosphorylation sites were identified in control hearts with a number of these residues not phosphorylated in HCM hearts (21). In addition, Jin et al identified acetylated, methylated, and trimethylated residues in human β-MHC using size-exclusion chromatography (SEC)/middle-down mass spectrometry (MS) (22).…”
Section: Introductionmentioning
confidence: 99%